Knowledge seeking and green supply chain management: The mediating role of green self-efficacy - Arif Prihasalma Roichnanti (Universitas Ahmad Dahlan, 2025)
Purpose-This study aims to examine the effect of knowledge seeking on green supply chain management and to investigate the mediating role of green self-efficacy. Although prior studies emphasize the importance of knowledge-related activities in promoting sustainable practices, empirical findings remain inconclusive regarding how such activities are translated into green supply chain implementation. Furthermore, prior research has largely overlooked the influence of internal cognitive factors in explaining this relationship. Methodology-This study adopted a quantitative research design and utilized a survey-based data collection method. The respondents consisted of owners and managers of manufacturing micro, small, and medium enterprises located in Yogyakarta, Indonesia selected through purposive sampling. The research instruments were developed by adapting established measurement scales from previous studies and were evaluated using a Likert-type scale. The collected data were analyzed through partial least squares–structural equation modeling using SmartPLS version 4 to assess the measurement model and examine the proposed hypotheses. Findings-The findings reveal that green self-efficacy exerts a positive and statistically significant influence on green supply chain management. In contrast, knowledge seeking shows no significant direct impact on green supply chain management and does not significantly affect green self-efficacy. As a result, green self-efficacy fails to function as a mediating variable in the relationship between knowledge seeking and green supply chain management. Research Limitations-This research is constrained by a cross-sectional research design, which limits the examination of temporal dynamics and reduces the ability to draw strong causal inferences among the studied variables. In addition, the use of self-reported data may introduce response bias, as perceived practices may differ from actual green supply chain implementation. Finally, the focus on manufacturing micro, small, and medium enterprises within a single regional context may limit the generalizability of the findings to other sectors or geographical settings. Novelty-This study offers novel insights by demonstrating that green self-efficacy plays a more decisive role than knowledge seeking in driving green supply chain management adoption. By integrating social cognitive theory into green supply chain research, this study challenges the assumption that knowledge acquisition automatically leads to sustainable practices and highlights the importance of internal cognitive readiness in sustainability-oriented decision-making, particularly in resource-constrained organizational contexts.